Project Evaluations and Decision Processes - Karine Nyborg (Statistics Norway, Research Department, 1995)
Cost-benefit analysis have been attacked by many critics because of its implicit ethical assumptions. The normative content of the method is at odds with the common attitude that economists should analyze how to reach given goals, while determination of the goals should be left to the politicians. This paper presents a descriptive model of decision makers' behavior, demonstrating that rational, benevolent politicians will only in special cases accept the evaluation of projects resulting from a cost-benefit analysis. An alternative approach to project evaluation, which allows individual decision makers to rank projects in accordance with their own ethical views, is presented. In this framework, estimates of willingness to pay are generally not required. On the other hand, information about groups that are significantly affected by the project, as well as physical unit information on changes in the supply of public goods, is crucial.
Keywords: A11; D61; D78; D83; H43; 330; Cost-benefit analysis; welfare judgements; information constraint.